2020
DOI: 10.17159/2519-0105/2020/v75no4a5
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of clinical experiences in endodontic access cavity preparations

Abstract: OBJECTIVES: The aim of this study was to gain understanding into the perceptions of undergraduate dental students regarding their levels of competence and confidence when preparing endodontic access cavities MATERIALS AND METHOD: Anonymous survey forms were given to 100 undergraduate dental students at Sefako Makgatho Health Sciences University, School of Oral Health Sciences. Students were asked to indicate their self-confidence level by using a 5-point Likert scale as 'not confident', 'manageable', 'comforta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Another study also evaluated the perceptions of undergraduate dental students regarding their levels of competence and confidence when preparing endodontic access cavities. The majority of the participants indicated their ease of performing endodontic access cavity preparation in anterior teeth, and the lowest confidence levels were indicated on multi-rooted posterior teeth [24] . The technical quality of RCTs performed by preclinical dental students showed that only a few procedures had acceptable technical quality [25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also evaluated the perceptions of undergraduate dental students regarding their levels of competence and confidence when preparing endodontic access cavities. The majority of the participants indicated their ease of performing endodontic access cavity preparation in anterior teeth, and the lowest confidence levels were indicated on multi-rooted posterior teeth [24] . The technical quality of RCTs performed by preclinical dental students showed that only a few procedures had acceptable technical quality [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the participants indicated their ease of performing endodontic access cavity preparation in anterior teeth, and the lowest confidence levels were indicated on multi-rooted posterior teeth. [24] The technical quality of RCTs performed by preclinical dental students showed that only a few procedures had acceptable technical quality. [25] While the present study did not evaluate the variable of self-confidence, the results of our research can be related to the existing literature, [26][27][28][29] where the level of education plays a role in increasing or decreasing the frequency of endodontic mishaps.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there were no statistically significant differences between the means of the students' self‐assessment grades of different types of teeth (anterior teeth, premolars and molars) except in the examination and diagnosis section, where the students gave themselves higher grades for molars. That was in contrast to previous studies that reported students had higher confidence in performing root canal treatment in anterior teeth compared with molars 39–41 . The undergraduate fourth year is considered the first year where students start to perform clinical root canal treatment on real patients.…”
Section: Discussionmentioning
confidence: 73%
“…That was in contrast to previous studies that reported students had higher confidence in performing root canal treatment in anterior teeth compared with molars. [39][40][41] The undergraduate fourth year is considered the first year where students start to perform clinical root canal treatment on real patients. Therefore, the close supervision by the instructors is expected in each clinical step.…”
Section: Ta B L Ementioning
confidence: 99%
“…The access cavity preparation training is crucial as students familiarise themselves with proper access preparation techniques and common procedural errors that could occur during the procedure -including perforation, gouging, overextension, and potentially others. 11 Access cavity competency is a necessity and an integral part of the clinical ability needed for root canal therapy. It requires delicate, specific hand skills, and the integrative design of the cavity based on radiographs and the clinical appearance of the tooth that is accessed.…”
Section: Introductionmentioning
confidence: 99%